Evaluasi Investasi Pendirian Cabang Usaha Dagang Lilin Bersinar - Danayanti, Devina; Sudana, I Putu (E-Jurnal Akuntansi; Vol 31 No 9 (2021)DO - 10.24843/EJA.2021.v31.i09.p17, 2021)
The purpose of this study is to determine the real performance of Antasura outlets in accordance with an investment feasibility study by reassessing ongoing projects to be able to determine the accuracy of past estimates, and to ensure that the company's economic resources are used as well as possible. This research was conducted at UD. Lilin Bersinar. The type of data used in this study is qualitative in the form of company history, company organizational structure, and business license and quantitative in the form of proceeds and initial investment value of the company. The analysis technique used is comparing the feasibility study report and post audit using the capital budgeting method. The results of the analysis show the realization of a payback period of 2,362 years, ARR of 22.32 persent, NPV of Rp.887,136,380, IRR of 13.21 Persent of feasibility study report at UD. Lilin Bersinar. Keywords: Investment; Post-audit; Capital Budgeting.